Faktor – Faktor yang Berhubungan dengan Pemilihan Alat Kontrasepsi IUD di Wilayah Kerja Puskesmas Payakabung Kecamatan Inderalaya Utara Kabupaten Ogan Ilir Tahun 2025. - Dela Marsela; Bina Aquari; Putu Lusita Nati Indriani; Intan Sari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
With an efficacy rate of up to 99.4 percent, the intrauterine device (IUD) is highly effective in reducing maternal mortality and limiting population growth. Hormonal IUDs have a duration of use of 3–5 years, while copper IUDs last for 5–10 years. The study referred to is an analytical observational cross-sectional study, meaning that the independent and dependent variables were measured simultaneously (Sastroasmoro & Ismael, 2014). This research was conducted at Payakabung Public Health Center, North Inderalaya District, Ogan Ilir Regency. The study was carried out from April to June 2025.The population of this study included all family planning acceptors in the working area of Payakabung Public Health Center in 2024, North Inderalaya District, Ogan Ilir Regency. Sampling was conducted using probability sampling with a simple random sampling technique. The Statistical Product and Service Solution (SPSS) software was used to perform the chi-square test for analysis. The selection of intrauterine contraceptive devices (IUDs) was significantly correlated with anxiety level, educational level, and employment status. The selection of IUDs was significantly associated with anxiety level (p-value = 0.028, α < 0.05). Educational level was significantly correlated with the adoption of IUD contraception (p-value = 0.023, α ≤ 0.05). Employment status was also significantly associated with the selection of IUDs (p-value = 0.028, α ≤ 0.05).